Phylogenetic relationships and morphology of the Pristimantis leptolophus species group (Amphibia: Anura: Brachycephaloidea), with the recognition of a new species group in Pristimantis Jiménez de la Espada, 1870 - González-Durán, Gustavo A.; Targino, Mariane; Rada, Marco; Grant, Taran (Zootaxa, 2017)
We evaluate the monophyly and phylogenetic relationships of the Pristimantis leptolophus species group and describe its external morphology, osteology, and some myological characteristics. We also compare the P. leptolophus species group to other related species groups. The P. leptolophus group is not monophyletic due to the inclusion of P. acatallelus, formerly believed to be part of the P. devillei group. The revised P. leptolophus group is composed of nine named species and six unnamed species. Based on our results, we recognize a new species group, the P. boulengeri species group, composed of eight species, many of which were previously assigned to the P. lacrimosus species group.